ANTIFUNGAL ACTIVITIES OF MODIFIED CHITOSAN WITH VANILLIC ACID AGAINST PLANT PATHOGENIC FUNGI, Fusarium solani AND Fusarium proliferatum. - Wan Roslina, Wan Yusof; Sumiyyah, Sabar; Awang Ahmad Sallehin, Awang Husaini (2023)
Modification of chitosan with phenolic acids has garnered increasing interest to obtain the new modified chitosan with greater potential and physicochemical as well as biological properties. In this study, modification of chitosan was achieved via free radical grafting between low molecular weight chitosan (LMwCS) and vanillic acid (VA). The ratio of VA in grafting was optimised while the amount of LMwCS and redox initiators were kept constant. Characterisations of the modified chitosan were conducted based on the grafting efficiency, vanillic acid content, chemical composition, and solubility at all pH range. The inhibitory effect of modified chitosan on the mycelia growth of Fusarium solani and Fusarium proliferatum was evaluated. The characterizations of the modified chitosan demonstrated that the modification between LMwCS with VA at ratio 0.5 had the highest content of VA. Similarly, LMwCS with VA at ratio 0.5 showed the greatest inhibitory effect towards the growth of F. solani and F. proliferatum. Overall, this study provides the preliminary findings of the new modified chitosan with vanillic acid for their application in the control of plant pathogenic fungi.